3, 5-Disubstituted Thiazolidine-2, 4-Diones: Design, Microwave-Assisted Synthesis, Antifungal Activity, and ADMET Screening. (September 2018) - Marc, Gabriel; Stana, Anca; Pîrnău, Adrian; Vlase, Laurian; Vodnar, Dan C.; Duma, Mihaela; Tiperciuc, Brînduşa; Oniga, Ovidiu
A series of 12 new thiazolidine-2, 4-dione derivatives were obtained by microwave-assisted synthesis. All compounds were physicochemically characterized by quantitative elemental C, H, N, S analysis and spectral data (mass spectrometry [MS], infrared [IR], and nuclear magnetic resonance [NMR]), with the results being in agreement with the expected data. An in vitro screening performed on Candida albicans ATCC 10231 showed their moderate antifungal activity, which was further investigated by determining the minimum inhibitory concentration and minimum fungicidal concentration values for the most active compounds on four strains of Candida . The molecular docking studies, performed against a fungal lanosterol 14α-demethylase, emphasized the importance of different molecular fragments in the compounds' structures for their antifungal activity. The synthesized compounds were subjected to in silico screening for the prediction of their absorption, distribution, metabolism, excretion, and toxicity (ADMET) and molecular properties. The results of the antifungal activity assays, docking study, and ADMET predictions revealed that the synthesized compounds are potential anti- Candida agents that might act by interacting with the fungal lanosterol 14α-demethylase and could be further optimized and developed as antifungal agents.